Webometric Analysis of Websites of Hindi Newspapers in India - Pradhan, Sandeep S. (Journal of Information and Knowledge, 2019)
Newspapers have great influence on society. They are important for communication and as a source of information to user. Using Alexa internet webometric analysis and evaluation of top Indian Hindi newspaper websites is the main purpose of this study. All newspaper websites searched in Alexa internet databank and related essential statistical data for traffic ranking, pages view, downloading speed and percentage of bounce, time spend on site, searching rate, and Indian and foreign visitor percentage were measured. Latter on this statistical data were analyzed. The final result of this study shows that NavBharat Times is having good traffic rank in India and globally also having highest links (63,775) and foreign user percentages (23.4%). Lokmat Samachar having fastest downloading speed (1.318 sec), maximum page views (12.90), lowest bounces rate (10.30%), highest estimated daily time spent on site (10:17) and highest percentage of visit from search engine (48.70%).